2012
DOI: 10.1016/s0972-6292(16)30462-4
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Tachycardia in Repaired Double Chambered Right Ventricle - Identification of the Substrate and Successful Ablation

Abstract: A 35 year old female presented with recurrent ventricular tachycardia 5 years after she had undergone surgical repair of double chambered right ventricle. Electroanatomical mapping showed a localised scar in the apex with double potentials and good pace map. Ablation here resulted in non-inducibility of ventricular tachycardia. We hypothesise that the scarring in the apex is the result of sustained pressure overload and becomes arrhythmogenic similar to the apical scar in patients with mid-ventricular hypertro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Some cases of arrhythmias after surgical correction of DCRV have also been reported. Selvaraj et al reported a 35-year-old female having surgically corrected DCRV who presented with non-sustained VT due to a right ventricular apical scar that developed from the DCRV surgical repair [6]. One patient with DCRV was found to have postoperative paroxysmal atrial fibrillation with rapid ventricular response [7].…”
Section: Discussionmentioning
confidence: 99%
“…Some cases of arrhythmias after surgical correction of DCRV have also been reported. Selvaraj et al reported a 35-year-old female having surgically corrected DCRV who presented with non-sustained VT due to a right ventricular apical scar that developed from the DCRV surgical repair [6]. One patient with DCRV was found to have postoperative paroxysmal atrial fibrillation with rapid ventricular response [7].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the journal, Selvaraj et al describe a case where the circuit of the ventricular tachycardia was mapped to a site far away from scar in a patient who had undergone ventriculotomy as a part of surgical correction of double-chambered right ventricle [ 9 ]. Myocardial fibrosis, as defined by the voltage map settings, showed scar at right ventricular apex in this case.…”
mentioning
confidence: 99%